Mechanoelectric sensitivity reveals destructive quantum interference in single-molecule junctions - Sebastiaan van der Poel; Juan Hurtado-Gallego; Matthias Blaschke; Rubén López-Nebreda; Almudena Gallego; Marcel Mayor; Fabian Pauly; Herre S. J. van der Zant; Nicolás Agraït (Nature Communications)
Abstract Quantum interference plays an important role in charge transport through single-molecule junctions, even at room temperature. Of special interest is the measurement of the destructive quantum interference dip itself. Such measurements are especially demanding when performed in a continuous mode of operation. Here, we use mechanical modulation experiments at ambient conditions to reconstruct the destructive quantum interference dip of conductance versus displacement. Simultaneous measurements of the Seebeck coefficient show a sinusoidal response across the dip without sign change. Calculations that include electrode distance and energy alignment variations explain both observations quantitatively, emphasizing the crucial role of thermal fluctuations for measurements under ambient conditions. Our results open the way for establishing a closer link between break-junction experiments and theory in explaining single-molecule transport phenomena, especially when describing sharp features in the transmission.